Participation and inclusiveness in process and design - Johannesson, Emma; Östlund, Maria (2020)
Who is included and has the right to shape public spaces is constantly contested through power struggles and expressions of politics and culture, where conflicting interests shape urban development. The public’s right to engage in the decision-making that affects different aspects of their lives has led to that public participation is now often seen as an important part of a democratic society. With the starting point in the Agenda 2030 goal of universal access to safe, inclusive, green public spaces, this case study looks into the inclusiveness in the participation process and design of two parks in Jaffna, Sri Lanka. In the urban upgrading programme funded by the World Bank, we found that in the case of Old Park the participation process included authorities and stakeholders with an economic interest in the project but no public, and in Sankiliyan Park limited to a group of people from an area with the highest socioeconomic status in the city. Through the limited width in the participation process, the imagined ‘public’ was recreated through the design to largely include the Tamil middle-class. Although local residents were stated as the primary target group in Old Park, features such as restaurants, fees, and shops with local handicrafts; to a larger extent responds to the aspirations from the Tamil middle-class, diaspora, tourists, and the developmentalism in the urban upgrading of Jaffna’s public space. Further, the case of Sankiliyan Park illustrates how the public spaces of Jaffna are subject to the post-conflict tensions between the Sinhalese and the Tamils. As the process of design continuously went through actors con-nected to the Government, this led to that the links to the LTTE were eliminated, and replaced with a compromised celebration of the Tamil identity in the public space. The sanction of one ethnic group through symbols and design can also lead to the exclusion of other minorities. With a French architect responsible for the design of Old Park, the study also revealed struggles with transnational design and participation processes and the increased need for public participation for the designer to understand the context. On the other hand, we also see an opportunity in the transnational design process to discover and highlight issues of inclusion and dictated norms, which can be beneficiary both ways and can help answer to the Agenda 2030 of universal access to public space.